2021
DOI: 10.3389/fimmu.2021.679897
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Alleviates Murine Experimental Colitis by Restoring Gut Microbiota and Inhibiting the LPS-TLR4-NF-κB Axis

Abstract: Intestinal microbiota dysbiosis is an established characteristic of ulcerative colitis (UC). Regulating the gut microbiota is an attractive alternative UC treatment strategy, considering the potential adverse effects of synthetic drugs used to treat UC. Kaempferol (Kae) is an anti-inflammatory and antioxidant flavonoid derived from a variety of medicinal plants. In this study, we determined the efficacy and mechanism of action of Kae as an anti-UC agent in dextran sulfate sodium (DSS)-induced colitis mice. DSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(80 citation statements)
references
References 63 publications
2
63
1
Order By: Relevance
“…It was reported that EVs could play a role in host-microbe r e s p o n s e s a n d r e g u l a t e t h e g u t m i c r o fl o r a ( 4 3 ) . Proteobacteria was reported to be the main phylum of pathogenic bacteria, which promoted the production of excessive pro-inflammatory cytokines and related to IBD pathogenesis (24,42). Akkermansia was a confirmed probiotic with anti-inflammatory effect by improving neutrophil infiltration and alleviating intestinal inflammation (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that EVs could play a role in host-microbe r e s p o n s e s a n d r e g u l a t e t h e g u t m i c r o fl o r a ( 4 3 ) . Proteobacteria was reported to be the main phylum of pathogenic bacteria, which promoted the production of excessive pro-inflammatory cytokines and related to IBD pathogenesis (24,42). Akkermansia was a confirmed probiotic with anti-inflammatory effect by improving neutrophil infiltration and alleviating intestinal inflammation (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that oral Q7-EVs down-regulated TLR4 and MyD88 gene expression compared with DSS-induced colitis mice ( Figure S4 ) . After binding to the ligand, MyD88-dependent signal transduction could lead to phosphorylation of NF-κB, thereby regulating the levels of transcription factors of IL-1β, IL-6, and TNF-α ( 24 ). It was speculated that Q7-EVs improved colitis by regulating the TLR4-MyD88-NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence for the role of kaempferol in attenuating inflammatory response mediated by NF- к B, indicating its protective effects on bone loss in postmenopausal osteoporosis by blocking TNF- α -induced nuclear translocation of the NF- к B subunit p65 from the cytoplasm to the nucleus [ 52 ]. And KP could suppress age-related NF- к B activation by inhibition of NF- к B subunit p65 translocation so as to restrain inflammatory response [ 53 ]. Some evidence showed that there was a negative correlation between dietary intake level of KP and serum CRP level, suggesting the key role of KP in reducing the risk of inflammation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…32 It is confirmed that kaempferol plays a protective role in colitis mice by regulating intestinal microbiota and toll-like receptor-related signaling pathways. 33 Stigmasterol has been shown to be an immunomodulator with great therapeutic potential. 34 Stigmasterol plays an important anti-inflammatory role and can reduce oxidative stress in a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%